ASSOCIATION BETWEEN STRESS, INSOMNIA, AND MENSTRUAL IRREGULARITIES AMONG MIDWIFERY STUDENTS, FACULTY OF MEDICINE, AIRLANGGA UNIVERSITY: Hubungan Tingkat Stres dan Insomnia dengan Ketidakteraturan Menstruasi pada Mahasiswi Kebidanan Fakultas Kedokteran Universitas Airlangga - Fadelia Bunga Lorenza; Kurnia Dwi Artanti; Vinitha Dwi Rahmasari; Wong Arkers Kwan Ching (Jurnal Berkala Epidemiologi, 2026)
Background: Menstrual problems affect an estimated 500 million people worldwide, with reported prevalence among schoolgirls and female university students ranging from 23% to 76.60%. In Indonesia, the prevalence has been reported as 11.70%. Academic pressure may contribute to stress and insomnia, which in turn may increase the risk of menstrual irregularities. Purpose: Analyze the direction and strength of the relationships between stress, insomnia, and menstrual irregularities among midwifery students at the Faculty of Medicine, Airlangga University. Methods: This observational analytic study used a cross-sectional design. Data were collected from 109 respondents selected through simple random sampling using validated and reliable questionnaires. Data normality was assessed using the Kolmogorov-Smirnov test, and associations between variables were examined using Spearman’s rank correlation test. Results: Among the respondents, 34% reported regular menstrual cycles, while 66% experienced menstrual irregularities. The normality test indicated that all variables were not normally distributed (menstrual irregularity p<0.01; stress level p=0.01; insomnia level p=0.01). Spearman’s rank correlation analysis showed significant positive correlations between stress and menstrual irregularities (p=0.00; r=0.48) and between insomnia and menstrual irregularities (p=0.00; r=0.32). These findings indicate that higher levels of stress and insomnia were associated with greater menstrual irregularities. The association was moderate for stress and weak for insomnia. Conclusion: Stress and insomnia were significantly associated with menstrual irregularities among midwifery students. These findings highlight the importance of stress reduction, sleep management, and regular reproductive health screening in this population.